Asthma Symptoms Do not Predict Spirometry - Robert L Cowie; Margot F Underwood; Stephen K Field (Canadian Respiratory Journal)
BACKGROUND: Asthma is a disease characterized by variable airflow obstruction, but the measurement of airflow is often omitted in the process of diagnosis and management of the disease.